2022
DOI: 10.3390/jcm11195910
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex in Left Atrial Indices for Prognosis of Heart Failure with Preserved Ejection Fraction

Abstract: Objective: We aim to clarify the differences in the association between re-admission for heart failure (HF) and left atrial (LA) overload indices by sex in heart failure and a preserved ejection fraction (HFpEF). Methods: We analyzed 898 HFpEF patients hospitalized for acute decompensated HF. Blood tests and transthoracic echocardiography were performed before discharge. The primary endpoint was re-admission for HF during the first year. Results: The ratio of diastolic elastance to arterial elastance (p = 0.01… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The significance of Ed/Ea as a prognostic risk factor may be reduced in HFpEF patients with AF because the calculation of Ed/Ea is based on the correct measurement of E/e , which should be carefully and precisely measured. The incidence of AF did not differ significantly in our patients (38%) [48] compared to the previous report (40%) [49]. E/e is correlated with invasive LV filling pressure and adequate reproducibility, even in patients with AF [50].…”
Section: Factors Affecting the Significance Of Ed/ea In The Prognosis...contrasting
confidence: 60%
See 2 more Smart Citations
“…The significance of Ed/Ea as a prognostic risk factor may be reduced in HFpEF patients with AF because the calculation of Ed/Ea is based on the correct measurement of E/e , which should be carefully and precisely measured. The incidence of AF did not differ significantly in our patients (38%) [48] compared to the previous report (40%) [49]. E/e is correlated with invasive LV filling pressure and adequate reproducibility, even in patients with AF [50].…”
Section: Factors Affecting the Significance Of Ed/ea In The Prognosis...contrasting
confidence: 60%
“…We recently reported that between-sex differences in the significance of Ed/Ea as a prognostic factor were observed in patients with HFpEF [48]. Ed/Ea was significant for readmission for HF during the first year in men, but not in women, in a multivariable analysis [48]. P for the interaction regarding Ed/Ea for this prognosis between sexes was significant.…”
Section: Factors Affecting the Significance Of Ed/ea In The Prognosis...mentioning
confidence: 89%
See 1 more Smart Citation
“…A decrease in the left atrial reservoir strain, as assessed using CMR, has been shown to be independently associated with time to adverse events in patients with restrictive cardiomyopathy [ 14 ]. A left atrial overload measured with echocardiography is an important prognostic factor for heart failure readmission during the first year after enrolment in patients with HFpEF, but indices relating to a left atrial overload differed by sex [ 15 ].…”
Section: Heart Failure and Ventricular Function Assessmentmentioning
confidence: 99%